Experimental study of the influence of short-term tamponade with perfluorine organic compounds on the bioelectric functional activity of the retina of the rabbit eye - Zhmurik , D. V.; Hramenko , N. I.; Slobodjanik , S. B.; Milienko , M. V. (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Perfluorine organic compounds (PFOC) possess valuable qualities for vitreoretinal surgery, and their application for short-term tamponade could expand indications to surgical treatment and improve results. However, there is no unequivocal opinion concerning the effect of PFOC on the functional condition of the retina. Purpose of the investigation is determination of peculiarities of the influence of short-term tamponade with PFOC (7 days) on the bioelectric functional activity of the retina in experiment, comparison of the PFOC effect and silicone 5700 cCm in dynamics by making ERG in different periods after the end of tamponade (7, 14, 30 days). Material and methods. The investigation was carried out in 6 Chinchilla rabbits (12 eyes). All animals were performed posterior closed subtotal vitrectomy with the subsequent tamponade (7 days) with PFOC (the right eye) and silicone viscosity 5700 cCm (the left eye). Electroretinography was made to all animal before the surgical intervention and after the end of tamponade in 7, 14 and 30 days. Results. While analyzing scotopic ERG there was revealed lengthening of the wave latency «B» 2 times in comparison with the initial data that made (48.8+5.8) ms and increase of the amplitude by 83 % (235.5+7.5 pV). In analysis ofphotopic ERG the wave «B» indices have changed — the latency time was extended by 52 %, that has made 40.2 ms and there was a tendency to increase its amplitude by 27%, (86.5+6.5 pV)for the 7-th day ofthe investigation. By the 14th day there was a tendency to normalization of ERG indices. Normalization of the functional condition of the central section and reduction in the activity of the photoreceptor layer ofthe retinal periphery by 18 % with preservation ofthe activity ofthe middle layer was observed by the 30th day. The comparative analysis of ERG indices in the group of silicone oil and PFOC revealed that indices of the maximal ERG in the group with silicone were lower by 37 % on the 7-th day of observation. By the 30th day of observation there was no statistically significant difference in two groups. Conclusions. There were determined peculiarities of the influence of the tamponade substances PFOC on the bioelectric functional activity of the retina of the rabbit eye in experiment in dynamics with a follow-up of 1 month after its removal. There was revealed lengthening of latency and increase of the amplitude of the middle layers of the peripheral and central retina as well as cone photoreceptors on the 7-th day; normalization of the functional condition of the central section and reduction in the activity of the photoreceptor layer of the retinal periphery by 18 % with preservation of the activity of the middle layer by the 30th day of follow-up. Comparative analysis of ERG has shown that the bioelectric activity of the retina of the rabbit had no differences in 30 days after removal of tamponade with PFOC and silicone 5700.